CT image reconstruction algorithms: A comprehensive survey. (3rd October 2019) - Zhang, Shu; Xia, Youshen
Summary: With the application of computed tomography (CT) technology to the clinic diagnosis and image‐guided surgeries, various CT image reconstruction algorithms were presented for enhancing CT image quality based on different dose acquisitions. For wide and effective uses, this paper is going to provide a comprehensive survey on representative CT image reconstruction algorithms, in the light of low‐dose and high‐dose acquisitions and algorithm performance, including their merits and limitations. The algorithm performance and complexity are discussed under Gaussian and Poisson noise environments, respectively. Finally, experimental results analyze the efficiency and performance of several popular CT image reconstruction algorithms in terms of computation time and accuracy.